Impairments to executive function in emerging adults with Huntington disease. Issue 2 (30th November 2022) - Pfalzer, Anna C; Watson, Kelly H; Ciriegio, Abagail E; Hale, Lisa; Diehl, Spencer; McDonell, Katherine E; Vnencak-Jones, Cindy; Huitz, Elizabeth; Snow, Abigail; Roth, Marissa C; Guthrie, Cara S; Riordan, Heather; et al.
Abstract : Background and objectives: The clinical diagnosis of Huntington disease (HD) is typically made once motor symptoms and chorea are evident. Recent reports highlight the onset of cognitive and psychiatric symptoms before motor manifestations. These findings support further investigations of cognitive function across the lifespan of HD sufferers. Methods: To assess cognitive symptoms in the developing brain, we administered assessments from the National Institutes of Health Toolbox Cognitive Battery, an age-appropriate cognitive assessment with population norms, to a cohort of children, adolescents and young adults with (gene-expanded; GE) and without (gene-not-expanded; GNE) the trinucleotide cytosine, adenine, guanine (CAG) expansion in the Huntingtin gene. These five assessments that focus on executive function are well validated and form a composite score, with population norms. We modelled these scores across age, and CAP score to estimate the slope of progression, comparing these results to motor symptoms. Results: We find significant deficits in the composite measure of executive function in GE compared with GNE participants. GE participant performance on working memory was significantly lower compared with GNE participants. Modelling these results over age suggests that these deficits occur as early as 18 years of age, long before motor manifestations of HD. Conclusions: This work provides strong evidence that impairments in executive function occur as early as the second decade of life, well before anticipated motor onset. Future investigations should delineate whether these impairments in executive function are due to abnormalities in neurodevelopment or early sequelae of a neurodegenerative process.